Effect of Gamma Radiation on Greasy and Scoured Wool, Irradiated in Mini-Bale Form - Jim Rapakgadi; Lawrance Hunter; Gawie Nothnagel; Anton Botha (Journal of Natural Fibers, 2022)
The effect of gamma radiation dose on certain properties of wool treated in either greasy or scoured form in mini-bales was investigated. Specific properties studied include color (yellowness and brightness), solubility (alkali solubility and urea-bisulfite solubility), fiber diameter and tensile properties (staple strength and bundle tenacity). The irradiation of the wool was performed in a commercial Cobalt-60 gamma irradiation facility to emulate practical irradiation conditions. It was found that gamma radiation dosages of up to ≈ 90 kGy did not significantly affect the fiber physical dimensions, namely fiber diameter and staple length. Alkali and urea-bisulfite solubility as well as yellowness and brightness, on the other hand, showed a systematic, almost linear, change with an increase in radiation dose. For a dose of ≈ 100 kGy, yellowness increased by ≈ 4.5 (Y-Z) units, brightness decreased by ≈ 7.5 Y units and alkali and urea-bisulfite solubility increased by ≈ 14% (absolute) above their zero dose values.